Limpyong tubig para sa maayong panglawas a radio public service announcement for Davao City Water District - Sayago, Cheska C.
Davao City Water District has been the main provider of potable tap water in the city by virtue of the Presidential Decree 198. They have been the sole provider of safe and clean tap water for so many years and are still continuing to provide clean water even to far flung areas. They have been trying to reach out the different rural districts in the city as they are still part of its jurisdiction, however, these areas are resistant of DCWD?s services. Even with the fact that they are experiencing health problems due to their current source of water, still, they are hesitant in taking a tap water connection from Davao City Water District primarily because of financial issues. To address this need, a radio public service announcement is produced to educate these rural communities on the importance of safe and clean drinking water for their health. Health is one of the primary concerns of the society, and addressing health concerns to the public requires an effective communication tool. Water being a basic necessity no longer needs any advertisement; however, the public should always be reminded of the importance of clean water through public service announcements. The researcher went through the processes of research, data gathering, script writing, recording, audio editing to be able to produce a radio public service announcement for Davao City Water District to promote the importance of clean and safe drinking water.
Thesis (B.A. Communication Arts) -- University of the Philippines Mindanao
Keywords: Communication Arts -- Media Arts